The Mentoring Relationship in an Advertising Agency: Mentors Training Mentees - Mădălina Buga-Moraru (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Advertising work meets significant challenges in terms of hiring young professionals that should properly match the job description due to the permanent progress in this field. Therefore, in spite of the academic background, the portfolio, and the training hours, young professionals need to be mentored for a while in order to adapt to labour market. The relationship between juniors and seniors might be difficult unless the latter understand and help them systematically. This paper aims to present obstacles and necessity of mentorship in an advertising agency from juniors' perspectives, when meeting seniors' attitude towards their young teams or when achieving their first tasks. Therefore, this research is conducted by using two complementary methods. Firstly, 9 focus groups were organized by interviewing students between 2017 and 2020. A second method is represented by a survey applied to juniors working in full-services and specialized agencies. Practically, this study means to emphasize the need for mentorship, expressed even at the end of Bachelor or Master studies, on the one hand, and the manner this has changed when respondents were hired in agencies, on the other hand. This survey leads to a very simple idea: young professionals require a short time of transition from the academic to the labour responsibility, especially in this field where only knowledge is not enough.
Keywords: M37; 330; Mentoring; professionals; advertising; agency; seniors; juniors